The Influence of Product Diversity and Sevice Quality on Consumer Satisfaction at the Citra Cosmetic Store in Gowa Regency - Murniati, Murniati; Moh. Aris Pasigai; Syarthini Indrayani (International Journal of Economic Research and Financial Accounting, 2024)
This is a type of quantitative research aimed at identifying and analyzing the “The Influence of Product Diversity and Sevice Quality on Consumer Satisfaction at the Citra Cosmetic Store in Gowa Regency”. The type of data used in this study is quantitative data obtained from the shared questionnaire and related to the problem studied. In this study, the data sources used in data collection include primary data and secondary data. The research instrument used in this study uses the Likert Scale method. Based on the results of the study using statistical calculations through the application Statistical Package for the Social Science (SPSS) version 29 on the impact of product diversity and quality of service on consumer satisfaction in the Cosmetic Image Shop in Gowa district, the results were obtained that the diversity of product has a positive and significant influence on customer satisfaction proved with a Sig. value 0.001 < 0.05 and a thitung value 26.581 > ttables 1.986. Quality of service also had a positive influence and significant impact on the satisfaction of consumers proved with the Sig. rating 0.001 < 0.05, and the thitung value 4.065 > ttabels 1.986, so it can be concluded that the hypothesis in this study is acceptable.